Echocardiographic and clinical markers of left ventricular ejection fraction and moderate or greater systolic dysfunction in left ventricular noncompaction cardiomyopathy. Issue 7 (25th March 2018) - Arenas, Ivan A.; Mihos, Christos G.; DeFaria Yeh, Doreen; Yucel, Evin; Elmahdy, Hany M.; Santana, Orlando
Abstract : Background: Left ventricular noncompaction (LVNC) is associated with progressive LV systolic dysfunction and dilated cardiomyopathy. We aimed to investigate the echocardiographic and clinical characteristics associated with LV ejection fraction (LVEF) and moderate or greater systolic dysfunction in patients with LVNC. Methods: Our institutional echocardiography database was retrospectively reviewed between 2008 and 2014, and 62 patients with LVNC were identified. Forty‐three (69%) had moderate or greater LV systolic dysfunction (LVEF ≤ 40%) and were compared with 19 (31%) patients with preserved or mildly reduced LVEF (>40%). Linear regression analyses were utilized to identify markers associated with LVEF. Results: The mean age was 63 ± 17 years and noncompacted‐to‐compacted ratio was 2.3 ± 0.5, and was larger in patients with LVEF ≤ 40% (2.4 vs 2.1; P = .02). Patients with LVEF ≤ 40% were older, had more congestive heart failure, significant QRS interval prolongation, and greater LV remodeling and worse mean global longitudinal strain (GLS). Multivariate regression analysis revealed increased age (standardized regression coefficient (β) = −0.17; P = .04) and QRS duration (β = −0.13; P = .08), congestive heart failure (β = −0.18; P = .04), and worsened GLS (β = −0.40; P = .001) were independently associated with decreased LVEF in the cohort (overall model fit R 2 = 0.71; P < .0001). Increased age (β = −0.49; P = .01) and QRS duration (β = −0.50; P = .002), and worsened GLS (β = −0.33; P = .04), were also associated with a lower LVEF in patients with LVEF > 40%. Conclusions: The independent markers associated with LVEF and moderate or greater LV systolic dysfunction in patients with LVNC, in particular GLS and QRS duration, may detect high‐risk candidates for more aggressive clinical surveillance and medical therapy.